Survey on Prediction System for Student Academic Performance using Educational Data Mining - et.al, Nilesh V. Ingale, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Grading students’ academic performance is a more difficult and challenging work which will help educators to keep track of progress of performance of students. For this the Educational Data mining (EDM) is a most active and demanding research field. It target is to finding of useful information from the educational dataset by using data mining techniques. Most important tasks of EDM are the prediction of the students’ performance. Various researchers all around the globe have published research work on prediction of students’ performance [1]. EDM plays an important role in the world of business to help the educational institution for the prediction as well as for make necessary decisions depends on the students’ academic performance. Now a day’s enhancement of students’ performance will affects the students’ career and also the reputation of the institute [2]. The main aim of this review paper is to explore the methodology developed and used by these researchers and the findings of their research work in uncomplicated and simplest manner. We presented a comparative study on the effectiveness from prediction of student’s performance by applying the EDM techniques. The study results make one important conclusion, which showing that the EDM methods are adequately effective for prediction of students’ academic performance, and these predictions are useful to make the necessary decisions and actions by management and teachers.[3]